Spatial evenness of fertilization and short-term volume growth responses of Scots pine and Norway spruce to fertilization intensity - Olli Muhonen; Heli Peltola; Annamari Laurén; Veli-Pekka Ikonen; Juha Nevalainen; Laura Pikkarainen; Antti Kilpeläinen; Samuli Launiainen; Marjo Palviainen (Silva Fennica)
We studied the spatial evenness of nitrogen (N) fertilizer and the effects of fertilization intensity on the short-term volume growth responses in two ground-fertilized Scots pine and two airborne-fertilized Norway spruce study sites on mesic (Myrtillus-type) upland forests in Eastern Finland. We also studied the relationships between measured fertilizer dose, N concentrations in the needles and soil organic (humus) layer, and volume growth of the trees. In each study site, we established three replicate 1 ha blocks for each fertilization treatment (0, 150 and 200 kg N ha–1). Each block contained three 200 m2 circular plots. The spatial evenness of the fertilizer was measured using textile funnels. The height, breast height diameter and vitality of the trees were measured annually. The nutrient concentrations in the needles and humus layer were measured once. Differences between the target and measured fertilizer doses were 3–10% for Scots pine and 11–22% for Norway spruce. At the Scots pine and Norway spruce sites, the volume growth was 0.4–2.1 and 1.8–2.6 m3 ha–1 a–1 higher with fertilization, respectively. The fertilizer dose correlated with the N concentrations in the needles and humus layer, and volume growth. Significant volume growth responses to the fertilization (p < 0.05) were found only in the Scots pine at Ilomantsi, possibly due to variations in the initial volume and the fertilizer dose realized between and within treatments. We expect that the differences in volume growth responses between fertilization treatments will increase over time.